Glove balloon uterine tamponade for post-partum haemorrhage: indigenous, readily available, cheap, easy to learn and practice, yet effective - Tasneem, Fasiha; Sharma, Vinutha M. (International Journal of Research in Medical Sciences, 2021)
Background: Postpartum haemorrhage (PPH) is still a nightmare in obstetrics. It is the leading cause of maternal mortality and morbidity accounting for one quarter of the maternal mortality worldwide. In a simple language, we can say PPH is allowing the delivered woman to bleed till death. Uterine atony is the cause in 80% of cases. Methods: This study is conducted in a tertiary care and teaching hospital between May 2019-2020. There were 5400 vaginal and 2100 caesarean sections conducted in our institute in the study period. 20 patients who underwent vaginal delivery and 12 patients of caesarean section had PPH. Only one patient had unsuccessful glove tamponade who underwent stepwise devascularisation for her survival. Hence the success rate of glove tamponade in our institute is found to be 95% (n=19). Results: We chose glove as it is simple, safe, least invasive, rapidly made without any expertise, non-irritant, doesn’t rupture easily, doesn’t slip and cost effective. We have manually tried out the capacity of the glove and found to be enormous, of 10 litres. After a successful insertion of glove tamponade, it is left in situ for 24 hours in our study. Conclusions: In this era of advanced medical services, it is annoying to say women still die of postpartum haemorrhage. Timely intervention (medical or surgical) in the golden hour can bring back many mothers back to life.